Effect on different growth regulators on shoot proliferation of garlic (Allium sativa L.) - Rosana, Santi; Budi Muljono, Julia Retno Andayani; , Ishak (IIUM Press, 2011)
Shoot formation of garlic (Allium sativum L.) tissue culture was studied in Murashige and Skoog (MS) and Gamborg's basal medium (B5) which are supplemented with a different combination of growth hormones namely 6-benzyl aminopurine (BAP) and a-Naphtaleneacetic acid (NAA) with and w'ithout cold pretreatments A stem-disc of shoot tips was used as explants for the induction ofgarlic shoot formation in the six weeks period.. A number of shoots, bulbs and fresh weight of bulb were observed. The shoot and bulbs formation were rapidly induced via organogenesis for the cold-pretreated bulbs at 4°C grown in a half MS media which contained 0.1 ppm of BAP in combination with 0.1 ppm NAA. Apparently, the induction of shoot and bulbs ofgarlic were influenced by temperature, hormones composition and nitrogen sour